Processing Queries over Multidimensional Encrypted Data - et. al., Norah Saud Al-Musib, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In new computing architectures, more and more data is outsourced to remote storage providers. When data outsourced, sensitive information becomes vulnerable to theft. Data owners want to make sure their data is safe from breaches by third parties, insider threats, and untrusted service providers. When queries are run over encrypted data, a certain level of secrecy is maintained. However, how to efficiently query encrypted multidimensional for data stored in an untrusted server environment residue a research challenge. In this paper, we propose an effective technique based on encryption by different keys in multidimensional mode to execute computations on data encrypted for multi principals. The proposed technique run queries directly without decrypting data as sensitive data are protected and insured.